Weight status and physical fitness in female soccer players: is there an optimal BMI? - Nikolaides, P. T. (Sport Sciences for Health, 2014)
The aim of this study was to examine the relationship between weight status and physical fitness in female soccer players. For this purpose, 54 soccer players [21.7 (4.0) years, 60.5 (7.0) kg, 164.3 (4.7) cm, mean (standard deviation)] underwent a physical fitness battery. To study this relationship we used a correlation analysis and compared three groups differing in body mass index (BMI): group A (BMI < 21 kg m-2), B (21 < BMI < 23 kg m-2) and C (BMI > 23 kg m-2). We found very large correlations between BMI and the components of somatotype (0.70 = |r| = 0.92, p < 0.001). BMI was also correlated with isometric muscle strength and leg muscle power (W) assessed by the Wingate anaerobic test (WAnT) and force-velocity test. In contrast, when muscle power was expressed as W kg-1, the correlation was negative. We also found an inverse relationship between BMI and fatigue index of WAnT (r = 0.36, p < 0.05): the higher the BMI, the higher was the decrease in performance during this 30 s all-out test. The comparison between A, B and C groups revealed differences in the same direction as the correlation analysis. We concluded that weight status is closely related with body composition, somatotype and leg muscle power. Therefore, achieving an optimal BMI might result in improvements with regard to physique and anaerobic power, and consequently in performance enhancement.